Statistical Optimization Of Process Parameters For Polygalacturonase Production By Bacillus Subtilis Kp10b (Applied Biological Research, 2022)
In present study the statistical optimization of process parameters for cost effective production of polygalacturonase (PGase) by Bacillus subtilis was  examined by using Plackett-Burman design (PBD) and central composite  design (CCD). Of the 9 factors, temperature, CaCO3 and KH2PO4 were  found significant by PBD and were further optimized by CCD. After  optimization, maximal PGase activity (272.87 Um L-1) was achieved at  40°C, 3.5 mM concentration of KH2PO4 and 6.5 mM concentration of  CaCO3. The results showed 2.95-fold increase in PGase activity of B. subtilis under optimized conditions. Thus, it may be concluded that  optimized medium is cost-effective and suitable for maximum production  and may be used for large-scale PGase production by B. subtilis KP10B.  The crude enzyme extracts of B. subtilis can be used in industry for fruit  juice clarification, waste water treatment and coffee fermentation.
Keywords: Bacillus subtilis; central composite design; Plackett-Burman design; polygalacturonase; statistical optimization